IMPLEMENTATION OF PREZI MEDIA BASED ON A SCIENTIFIC APPROACH TO SCIENTIFIC LITERACY - Wahana Panjang Nugraha; Ellyna Hafizah; Yasmine Khairunnisa (Sean Institute, 2023)
Scientific Literacy is needed to analyze information or scientific issues that arise in society. The purposes of this study are: 1) to know that there are differences in scientific Literacy between classes taught using Prezi media based on a scientific approach and one taught using conventional teaching methods; 2) to find out the difference in scientific Literacy before and after using the prezi media based on a scientific approach; and 3) to know the effect of using Prezi media based on a scientific approach on scientific Literacy. The type of research used was quantitative research with a quasi-experimental design with a non-equivalent control group design. The sample was chosen using a purposive sampling technique to determine the control and experimental classes. The data in this study were collected from tests in the form of scientific literacy questions and questionnaires for students' opinions on the Prezi media. The data analysis techniques used to test hypotheses are independent sample t-test, paired sample t-test, and simple linear regression. The results of the study show 1) there is a difference in scientific Literacy in the control class and the experimental class with an average value of 72.17 and 80.71, respectively; 2) there is a difference in scientific Literacy before and after using Prezi media based on a scientific approach increased from 70.29 to 80.71; And 3) there is an influence on the use of prezi media based on a scientific approach to scientific Literacy of 90.5%. The use of Prezi media based on a scientific approach has an influence and can increase students' Scientific Literacy.